Inflammation and cancer - Aggarwal, Bharat B.; Sung, Bokyung; Gupta, Subash Chandra; Aggarwal, Bharat B. (Advances in Experimental Medicine and Biology, 2014)
This volume examines in detail the role of chronic inflammatory processes in the development of several types of cancer. Leading experts describe the latest results of molecular and cellular research on infection, cancer-related inflammation, and tumorigenesis. Further, the clinical significance of these findings in preventing cancer progression and approaches to treating the diseases are discussed. Individual chapters cover cancer of the lung, colon, breast, brain, head and neck, pancreas, prostate, bladder, kidney, liver, cervix, and skin as well as gastric cancer, sarcoma, lymphoma, leukemia, and multiple myeloma.